Land Control, Authority and Political Economy, and a Planned Petroleum Infrastructure Project in Timor-Leste - Alex Grainger (Jember University Press, 2017)
Land in Timor-Leste had been a subject of national importance even before the government first announced a planned petroleum infrastructure ‘mega-project’ in 2009, the ‘Tasi Mane’ project, on the country’s south coast in Suai, Betano and Beaco. This project has brought again into sharp relief the question of land and its control. Much recent work has focussed on ‘land grabs’ or how foreign capital and the state have played a significant role in dispossessing smallholders of arable land in other settings. This paper highlights three aspects which are inherent in the process of control. First, authority lies at the heart of land control alongside political-economic factors that lead to relocation of residents from land in project areas. Second, problems of recognition of land rights in project areas have led to more strident claims to authority locally. This issue I demonstrate by showing the historical legacy of two communities that occupy Beaco land. Third, the case study of the two communities sheds light on the social relations inherent in local property relations and subsequent disputes catalysed by contests over land control.